Performance analysis of a solar-hydrogen driven multigeneration system - S. Erzen; E. Açıkkalp; A. Hepbasli (Energy Reports, 2020)
Environmental concerns have gained great attention in the last decades, especially the global warming caused by usage of fossil fuels mostly. Renewable energy sources are the most reasonable way to decreasing the fossil fuel usage as a primary source and to preventing its environmental effects. In this regard, renewable source multigeneration systems seem to be an alternative. In this paper, a solar driven multigeneration system consisting of PV/T panels, a hydrogen fueled diesel engine generator, an electrolyzer, a hydrogen compressor, a hydrogen storage tank, batteries, an air cooled chiller, a hydrogen combustor, a water storage tank, and a control systems is considered. The simulation of this system is performed through TRNSYS 18. Outputs from the proposed system are heating, cooling, electricity and hydrogen. The performance analysis is done for Izmir, which is the third biggest city in Turkey by population while the obtained results are evaluated over a period of one year.
Keywords: 330; Hydrogen; Air cooling chiller; Multigeneration; Solar energy